1996
DOI: 10.1266/ggs.71.63
|View full text |Cite
|
Sign up to set email alerts
|

Variations in glutelin and high molecular weight endosperm proteins among subspecies of rice (Oryza sativa L.) detected by two-dimensional gel electrophoresis.

Abstract: Variations in endosperm polypeptides among 16 cultivars of rice were analyzed by two-dimensional gel electrophoresis. One glutelin alpha-subunit (alpha 8) with a molecular mass of 32.5 kDa was exclusively present in indica cultivars. By contrast, the glutelin alpha 3 subunit, with a molecular mass of 32 kDa, was present only in japonica and javanica cultivars. Glutelin alpha-subunits alpha 5a and alpha 5b, which have a molecular mass of 32 kDa and slightly different isoelectric points, differed among rice subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…van der Borght et al (2006) reported the MW of a subunit as 32 kDa and b subunit as 25 kDa. The precursor band of around 58 kDa (Wx proteins) has been reported to express strongly in Indica cultivars compared to those of Japonica and Javanica (Abe, Gusti, Ono, & Sasahara, 1996). Accelerated aging did not have an apparent effect on the MW profiles of the extracted glutelin of Thai rice cultivars, both under non-reducing and reducing conditions.…”
Section: Resultsmentioning
confidence: 87%
“…van der Borght et al (2006) reported the MW of a subunit as 32 kDa and b subunit as 25 kDa. The precursor band of around 58 kDa (Wx proteins) has been reported to express strongly in Indica cultivars compared to those of Japonica and Javanica (Abe, Gusti, Ono, & Sasahara, 1996). Accelerated aging did not have an apparent effect on the MW profiles of the extracted glutelin of Thai rice cultivars, both under non-reducing and reducing conditions.…”
Section: Resultsmentioning
confidence: 87%
“…In rice, protein quality is an important determining value in the nutrient value of cooked rice, and a first study to determine precise varietal and subspecific variations among japonica (6), indica (6), and javanica (4) cultivars, using rice-endosperm proteins was performed in 1996 (Abe et al, 1996). Variations in endosperm polypeptides among these rice cultivars were analyzed by 2-DGE.…”
Section: A Cultivar Identificationmentioning
confidence: 99%
“…Several successful attempts were made, using 2-DE to characterize closely related lines of durum wheat [19], flour allergens in bread wheat cultivars [20], different lines of barley [21] differing in malting quality [22], cultivars of cultivated and wild rice [23,24], genotypes of maize [25,26], of sugar cane [27], of Vigna angularis [28] or of carrots [29]. Van Telgen and van Loon [30] examined the chromatin-associated proteins from leaves of different species and varieties of Nicotiana differing in their sensitivity towards tobacco mosaic virus (TMV).…”
Section: Genetic Diversitymentioning
confidence: 99%